(untitled) (Journal of actual problems of jurisprudence, 2018)
This article analyzes the current situation in the quasi-public and private sectors. Particularly the issues of regulatory issues of corruption prevention in the quasi-public and private sector, proposed measures for the prevention of corruption-related crimes in the quasi-public and private sectors. Key words: corruption, prevention of corruption, corruption in the quasi-public sector, corruption in the private sector, measures to prevent.